Humeral Shaft Fracture Treatment in the Elite Throwing Athlete: A Unique Application of Flexible Intramedullary Nailing. (28th November 2013) - Lee, Christopher S.; Davis, Shane M.; Ho, Hoang-Anh; Fronek, Jan
Abstract : Humeral shaft stress fractures are being increasingly recognized as injuries that can significantly impact throwing mechanics if residual malalignment exists. While minimally displaced and angulated injuries are treated nonoperatively in a fracture brace, the management of significantly displaced humeral shaft fractures in the throwing athlete is less clear. Currently described techniques such as open reduction and internal fixation with plate osteosynthesis and rigid antegrade/retrograde locked intramedullary nailing have significant morbidity due to soft tissue dissection and damage. We present a case report of a high-level baseball pitcher whose significantly displaced humeral shaft stress fracture failed to be nonoperatively managed and was subsequently treated successfully with unlocked, retrograde flexible intramedullary nailing. The athlete was able to return to pitching baseball in one year and is currently pitching in Major League Baseball. We were able to recently collect 10-year follow-up data.